Impact of noncoding RNAs on cancer directed immune therapies: Now then and forever. Issue 7 (8th June 2022) - Roy, Roshan Kumar; Yadav, Rakhi; Sharma, Uttam; Wasson, Mishi Kaushal; Sharma, Ashok; Tanwar, Pranay; Jain, Aklank; Prakash, Hridayesh
Abstract: Accumulating evidence demonstrates that the host genome's epigenetic modifications are essential for living organisms to adapt to extreme conditions. DNA methylation, covalent modifications of histone and interassociation of noncoding RNAs facilitate the cellular manifestation of epigenetic changes in the genome. Out of various factors involved in the epigenetic programming of the host, noncoding RNAs (ncRNAs) such as microRNA (miRNA), long noncoding RNA (lncRNA), circular RNA, snoRNA and piRNA are new generation noncoding molecules that influence a variety of cellular processes like immunity, cellular differentiation and tumor development. During tumor development, temporal changes in miRNA/lncRNA rheostat influence sterile inflammatory responses accompanied by the changes in the carcinogenic signaling in the host. At the cellular level, this is manifested by the upregulation of inflammasome and inflammatory pathways, which promotes cancer‐related inflammation. Given this, we discuss the potential of lncRNAs, miRNAs, circular RNA, snoRNA and piRNA in regulating inflammation and tumor development in the host. Abstract :